Three-dimensional graphene-reinforced carbon-based composite material and method for preparing the same
Patent Information
- Application Number
- CN202611052843.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]石墨烯作为一种二维碳纳米材料,具有极高的导电率和热导率,但将其直接掺杂到碳基体中时,容易发生团聚,难以形成有效的三维导电网络,且石墨烯与碳基体之间的界面结合较弱
[0021]本发明利用炭纤维表面三维石墨烯网络作为中间导电层,并在其表面原位生长氧化银纳米片,再通过碳基体致密化处理使碳基体填充并包覆于三维编织体孔隙中,最终形成“炭纤维-三维石墨烯-氧化银纳米片-碳基体”多尺度连续导电网络。相较于仅获得独立三维石墨烯纤维的已有技术,本发明的区别在于将三维石墨烯网络嵌入受电弓碳滑板用致密化碳基复合材料体系中,并通过氧化银纳米片实现石墨烯网络与碳基体之间的导电桥接和界面锚固。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a three-dimensional graphene-reinforced carbon-based composite material and its preparation method. Background Technology
[0002] Carbon-based composite materials (such as carbon-graphite materials and C / C composites) are ideal for sliding electrical contact components of electric locomotives, such as pantograph contact plates and motor brushes, due to their excellent self-lubricating properties and good electrical conductivity. However, with the increase in high-speed train operating speeds (350 km / h and above) and traction power, the pantograph-catenary system faces problems such as increased disconnection rate and unstable current collection, leading to frequent high-temperature arc erosion between the contact plate and the contact wire. Furthermore, the Joule heating effect accompanying high-power transmission is exacerbated, requiring the contact plate material to possess both high electrical conductivity to reduce contact resistance and high thermal conductivity to quickly dissipate frictional and arcing heat and prevent matrix oxidation failure.
[0003] Graphene, as a two-dimensional carbon nanomaterial, possesses extremely high electrical and thermal conductivity. However, when directly doped into a carbon matrix, it is prone to agglomeration, making it difficult to form an effective three-dimensional conductive network. Furthermore, the interfacial bonding between graphene and the carbon matrix is weak. In addition, the difference in thermal expansion coefficients between graphene and the carbon matrix leads to the formation of microcracks and pores at the interface during high-temperature carbonization and service thermal shock, resulting in severe carrier interface scattering effects, hindering electron transport and reducing load transfer efficiency.
[0004] Therefore, how to construct a carbon-based composite material with continuous conductive channels and high interfacial bonding strength is a technical problem that urgently needs to be solved. Summary of the Invention
[0005] The purpose of this invention is to provide a three-dimensional graphene-reinforced carbon-based composite material and its preparation method, so as to improve the above-mentioned problems. To achieve the above objective, the technical solution adopted by this invention is as follows:
[0006] In a first aspect, this application provides a method for preparing a three-dimensional graphene-reinforced carbon-based composite material, comprising:
[0007] Mesophase pitch-based carbon fibers are prepared into three-dimensional carbon fiber braids using a three-dimensional weaving process.
[0008] Using methane or acetylene as a carbon source, chemical vapor deposition is performed on three-dimensional carbon fiber weaving to grow a three-dimensional graphene network in situ on the surface of the carbon fiber, thus obtaining a three-dimensional graphene / carbon fiber preform.
[0009] The three-dimensional graphene / carbon fiber preform was placed in a solution containing a silver precursor, and silver oxide nanosheets were grown in situ on the surface of the three-dimensional graphene network through a hydrothermal reaction to obtain a three-dimensional graphene / carbon fiber preform modified with silver oxide nanosheets.
[0010] A matrix densification treatment was performed on a three-dimensional graphene / carbon fiber preform modified with silver oxide nanosheets to obtain a three-dimensional graphene-reinforced carbon-based composite material.
[0011] Optionally, the three-dimensional weaving process is selected from either three-dimensional orthogonal weaving or three-dimensional four-way weaving.
[0012] Optionally, the monofilament diameter of the mesophase pitch-based carbon fiber is 5–10 μm, and the porosity of the three-dimensional carbon fiber braid is 50%–80%.
[0013] Optionally, the process parameters for the chemical vapor deposition are: deposition temperature 800–1200℃, deposition time 10–60 min.
[0014] Optionally, the carbon source gas flow rate for the chemical vapor deposition is 100–500 sccm.
[0015] Optionally, the silver-containing precursor solution is one of silver nitrate solution, silver acetate solution, or silver ammonia solution, and the mass of the silver oxide nanosheets accounts for 1 to 15% of the mass of the three-dimensional graphene.
[0016] Optionally, the process parameters for the hydrothermal reaction are: reaction temperature 150-200℃, reaction time 8-15h.
[0017] Optionally, the matrix densification treatment employs chemical vapor infiltration or liquid phase impregnation-carbonization.
[0018] Optionally, the liquid-phase impregnation-carbonization method includes: immersing the preform in an impregnation solution of phenolic resin or mesophase pitch, impregnating under vacuum for 1–4 hours, and then carbonizing at 800–1000°C for 1–3 hours, repeating the impregnation and carbonization process until the material density reaches 1.6–2.0 g / cm³. 3 .
[0019] Secondly, this application also provides a three-dimensional graphene-reinforced carbon-based composite material, which is prepared by the above-described preparation method.
[0020] The beneficial effects of this invention are as follows:
[0021] This invention utilizes a three-dimensional graphene network on the surface of carbon fibers as an intermediate conductive layer, and grows silver oxide nanosheets in situ on its surface. Then, a carbon matrix densification treatment is applied to fill and encapsulate the pores of the three-dimensional braid, ultimately forming a multi-scale continuous conductive network of "carbon fiber-three-dimensional graphene-silver oxide nanosheets-carbon matrix". Compared to existing technologies that only obtain independent three-dimensional graphene fibers, this invention differs in that it embeds the three-dimensional graphene network into a densified carbon-based composite material system for pantograph carbon sliders, and uses silver oxide nanosheets to achieve conductive bridging and interfacial anchoring between the graphene network and the carbon matrix.
[0022] This invention further grows silver oxide nanosheets in situ on the surface of three-dimensional graphene. On the one hand, the layered structure fills the structural defects on the graphene surface, reducing phonon scattering and carrier scattering at the interface. On the other hand, the silver oxide nanosheets form layered overlaps, mechanical interlocking, and silver-based electronic bridging with the densified carbon matrix, effectively improving the interfacial bonding strength between the reinforcing phase and the matrix. Compared to particulate conductive fillers such as silver nanoparticles, silver oxide nanosheets are not randomly dispersed as isolated particles, but exist as an interfacial modification layer on the surface of the three-dimensional graphene network. This significantly improves the flexural and compressive strength of the material while enhancing conductivity.
[0023] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing embodiments of the invention. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations. Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0025] It should be noted that similar labels and letters below indicate similar items; therefore, once an item is defined in one, it does not need to be further defined and explained thereafter.
[0026] Existing pure carbon sliding plates suffer from high resistivity and low mechanical properties; while traditional metal-impregnated sliding plates offer better conductivity, they suffer from high density and poor lubrication. Research indicates that constructing continuous conductive channels within a carbon matrix and enhancing the interfacial bonding strength between the reinforcing phase and the matrix are key to improving the overall performance of composite materials. However, existing carbon-based composites suffer from technical challenges such as the tendency of conductive fillers to agglomerate and low interfacial bonding strength, making it difficult to simultaneously achieve both high conductivity and good mechanical properties.
[0027] To address the aforementioned technical problems, this invention provides a three-dimensional graphene-reinforced carbon-based composite material and its preparation method, with specific embodiments as follows:
[0028] Example 1:
[0029] A method for preparing a three-dimensional graphene-reinforced carbon-based composite material, comprising:
[0030] S1. Constructing a three-dimensional carbon fiber braided skeleton: Mesophase pitch-based carbon fiber (monofilament diameter 7μm, tensile strength 3.5GPa) was selected and a three-dimensional four-way braiding process was adopted to prepare a three-dimensional carbon fiber braid with a size of 100mm×100mm×20mm and a porosity of 65%.
[0031] S2. In-situ growth of a three-dimensional graphene network: The braided structure obtained in step S1 is placed in a chemical vapor deposition furnace and heated to 1000°C under an argon atmosphere. Methane gas is introduced (flow rate 300 sccm), and deposition is carried out for 30 min. A three-dimensional graphene network is grown on the surface of the carbon fiber, resulting in a three-dimensional graphene / carbon fiber preform. The graphene nanosheets are interconnected in an upright manner on the carbon fiber surface, forming a continuous three-dimensional network structure. In this embodiment, the three-dimensional graphene network mainly serves as an intermediate layer for subsequent silver oxide nanosheet loading and the interface connection between the carbon matrix and the matrix.
[0032] S3. Surface modification: The preform obtained in step S2 is placed in a 5 mg / mL silver ammonia precursor solution, the pH is adjusted to 9-10 and then transferred to a high-temperature reactor. The preform is hydrothermally reacted at 180°C for 12 h to allow silver oxide nanosheets to grow in situ along the edges and defect sites of the three-dimensional graphene sheets, thus obtaining a preform modified with silver oxide nanosheets.
[0033] S4. Matrix densification: The preform obtained in step S3 is placed in a phenolic resin impregnation solution and impregnated for 2 hours under a vacuum of -0.09 MPa. After removal, it is carbonized at 1000℃ for 2 hours. The impregnation-carbonization cycle is repeated 3 times to obtain the final composite material.
[0034] The density of the composite material prepared in this embodiment was tested to be 1.82 g / cm³. 3The resistivity is 9.2 μΩ·m and the flexural strength is 91 MPa. Compared with the pure carbon-based composite material without three-dimensional graphene (resistivity 18.5 μΩ·m, flexural strength 52 MPa), the resistivity is reduced by about 50% and the flexural strength is increased by about 75%.
[0035] Example 2:
[0036] A method for preparing a three-dimensional graphene-reinforced carbon-based composite material, comprising:
[0037] S1. Constructing a three-dimensional carbon fiber braided skeleton: Mesophase pitch-based carbon fiber (monofilament diameter 7μm, tensile strength 3.5GPa) was selected and a three-dimensional four-way braiding process was adopted to prepare a three-dimensional carbon fiber braid with a size of 100mm×100mm×20mm and a porosity of 65%.
[0038] S2. In-situ growth of a three-dimensional graphene network: The braided structure obtained in step S1 is placed in a chemical vapor deposition furnace and heated to 1000°C under an argon atmosphere. Methane gas is introduced (flow rate 300 sccm), and deposition is carried out for 30 min. A three-dimensional graphene network is grown on the surface of carbon fibers, resulting in a three-dimensional graphene / carbon fiber preform. Graphene nanosheets are interconnected in an upright manner on the carbon fiber surface, forming a continuous three-dimensional network structure. In this embodiment, this three-dimensional graphene network mainly serves as an intermediate layer for subsequent silver oxide nanosheet loading and the interface connection between the carbon matrix and the substrate.
[0039] S3. Surface modification: The preform obtained in step S2 was placed in a 1 mg / mL silver ammonia precursor solution, the pH was adjusted to 9-10 and then transferred to a high-temperature reactor. The mixture was hydrothermally reacted at 170°C for 10 h. Compared with Example 1, the loading of silver oxide nanosheets was reduced accordingly.
[0040] S4. Matrix densification: The preform obtained in step S3 is placed in a phenolic resin impregnation solution and impregnated for 2 hours under a vacuum of -0.09 MPa. After removal, it is carbonized at 1000℃ for 2 hours. The impregnation-carbonization cycle is repeated 3 times to obtain the final composite material.
[0041] The density of the composite material prepared in this embodiment was tested to be 1.84 g / cm³. 3 It has a resistivity of 10.6 μΩ·m and a flexural strength of 86 MPa.
[0042] Example 3:
[0043] A method for preparing a three-dimensional graphene-reinforced carbon-based composite material, comprising:
[0044] S1. Constructing a three-dimensional carbon fiber braided skeleton: Mesophase pitch-based carbon fiber (monofilament diameter 7μm, tensile strength 3.5GPa) was selected and a three-dimensional four-way braiding process was adopted to prepare a three-dimensional carbon fiber braid with a size of 100mm×100mm×20mm and a porosity of 65%.
[0045] S2. In-situ growth of a three-dimensional graphene network: The braided structure obtained in step S1 is placed in a chemical vapor deposition furnace and heated to 900°C under an argon atmosphere. Methane gas is introduced (flow rate 300 sccm), and deposition is carried out for 20 min. A three-dimensional graphene network is grown on the surface of carbon fibers, resulting in a three-dimensional graphene / carbon fiber preform. Graphene nanosheets are interconnected in an upright manner on the carbon fiber surface, forming a continuous three-dimensional network structure. In this embodiment, this three-dimensional graphene network mainly serves as an intermediate layer for subsequent silver oxide nanosheet loading and the interface connection between the carbon matrix and the substrate.
[0046] S3. Surface modification: The preform obtained in step S2 was placed in a 1 mg / mL silver ammonia precursor solution, the pH was adjusted to 9-10 and then transferred to a high-temperature reactor. The mixture was hydrothermally reacted at 170°C for 10 h. Compared with Example 1, the loading of silver oxide nanosheets was reduced accordingly.
[0047] S4. Matrix densification: The preform obtained in step S3 is placed in a phenolic resin impregnation solution and impregnated for 2 hours under a vacuum of -0.09 MPa. After removal, it is carbonized at 1000℃ for 2 hours. The impregnation-carbonization cycle is repeated 3 times to obtain the final composite material.
[0048] The resistivity of the composite material prepared in this embodiment is 12.5 μΩ·m and the flexural strength is 78 MPa, according to the test results.
[0049] Example 4:
[0050] A method for preparing a three-dimensional graphene-reinforced carbon-based composite material, comprising:
[0051] S1. Constructing a three-dimensional carbon fiber braided skeleton: Mesophase pitch-based carbon fiber (monofilament diameter 7μm, tensile strength 3.5GPa) was selected and a three-dimensional four-way braiding process was adopted to prepare a three-dimensional carbon fiber braid with a size of 100mm×100mm×20mm and a porosity of 50%.
[0052] S2. In-situ growth of a three-dimensional graphene network: The braided structure obtained in step S1 is placed in a chemical vapor deposition furnace and heated to 1200°C under an argon atmosphere. Methane gas is introduced (flow rate 500 sccm), and deposition is carried out for 40 min. A three-dimensional graphene network is grown on the surface of the carbon fiber, resulting in a three-dimensional graphene / carbon fiber preform. The graphene nanosheets are interconnected in an upright manner on the carbon fiber surface, forming a continuous three-dimensional network structure. In this embodiment, this three-dimensional graphene network mainly serves as an intermediate layer for subsequent silver oxide nanosheet loading and the interface connection between the carbon matrix and the carbon fiber.
[0053] S3. Surface modification: The preform obtained in step S2 was placed in a 3 mg / mL silver ammonia precursor solution, the pH was adjusted to 9-10, and then transferred to a high-temperature reactor. The preform was hydrothermally reacted at 200°C for 8 hours, compared to Example 1.
[0054] S4. Matrix densification: The preform obtained in step S3 is placed in a phenolic resin impregnation solution and impregnated for 1 hour under a vacuum of -0.09 MPa. After removal, it is carbonized at 800℃ for 3 hours. The impregnation-carbonization cycle is repeated 3 times to obtain the final composite material.
[0055] The density of the composite material prepared in this embodiment was tested to be 1.81 g / cm³. 3 It has a resistivity of 11.3 μΩ·m and a flexural strength of 88 MPa.
[0056] Example 5:
[0057] A method for preparing a three-dimensional graphene-reinforced carbon-based composite material, comprising:
[0058] S1. Constructing a three-dimensional carbon fiber braided skeleton: Mesophase pitch-based carbon fiber (monofilament diameter 7μm, tensile strength 3.5GPa) was selected and a three-dimensional four-way braiding process was adopted to prepare a three-dimensional carbon fiber braid with a size of 100mm×100mm×20mm and a porosity of 80%.
[0059] S2. In-situ growth of a three-dimensional graphene network: The braided structure obtained in step S1 is placed in a chemical vapor deposition furnace and heated to 800°C under an argon atmosphere. Methane gas is introduced (flow rate 100 sccm), and deposition is carried out for 35 min. A three-dimensional graphene network is grown on the surface of carbon fibers, resulting in a three-dimensional graphene / carbon fiber preform. Graphene nanosheets are interconnected in an upright manner on the carbon fiber surface, forming a continuous three-dimensional network structure. In this embodiment, this three-dimensional graphene network mainly serves as an intermediate layer for subsequent silver oxide nanosheet loading and the interface connection between the carbon matrix and the substrate.
[0060] S3. Surface modification: The preform obtained in step S2 is placed in a 7 mg / mL silver ammonia precursor solution, the pH is adjusted to 9-10 and then transferred to a high-temperature reactor. The preform is hydrothermally reacted at 150°C for 15 h to allow silver oxide nanosheets to grow in situ along the edges and defect sites of the three-dimensional graphene sheets, thus obtaining a preform modified with silver oxide nanosheets.
[0061] S4. Matrix densification: The preform obtained in step S3 is placed in a phenolic resin impregnation solution and impregnated for 4 hours under a vacuum of -0.09 MPa. After removal, it is carbonized at 900℃ for 3 hours. The impregnation-carbonization cycle is repeated 3 times to obtain the final composite material.
[0062] The density of the composite material prepared in this embodiment was tested to be 1.86 g / cm³. 3 It has a resistivity of 9.2 μΩ·m and a flexural strength of 95 MPa.
[0063] Comparative Example 1:
[0064] This comparative example is basically the same as Example 1, except that step S2 is omitted, the three-dimensional graphene network is not grown, and the carbon fiber braid is directly densified after surface modification.
[0065] The resistivity of the composite material prepared in this comparative example was 18.5 μΩ·m, and the flexural strength was 52 MPa.
[0066] Comparative Example 2:
[0067] This comparative example is basically the same as Example 1, except that step S3 is omitted and no surface modification is performed.
[0068] The resistivity of the composite material prepared in this comparative example was 15.2 μΩ·m, and the flexural strength was 65 MPa, according to the test results.
[0069] As can be seen, the composite materials prepared in Examples 1-5 of this invention are significantly superior to the comparative examples in terms of resistivity and flexural strength. Comparative Example 1 did not construct a three-dimensional graphene network, resulting in poor conductivity. Compared to Comparative Example 2 (without surface modification), Example 1, through a surface modification process, achieved a significant 44% reduction in resistivity while simultaneously increasing flexural strength by 31%, breaking the traditional trade-off between conductivity and mechanical properties in carbon / graphite composite materials. This is attributed to the effective transfer of load and the construction of a highly efficient conductive network by the interface modification layer.
[0070] The composite material prepared by this invention has high electrical conductivity, high thermal conductivity and excellent mechanical properties, which can meet the stringent service requirements of the pantograph contact plate of high-speed railway under the multi-field coupling conditions of electric-thermal-mechanical fields, and has important engineering application value.
[0071] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing a three-dimensional graphene-reinforced carbon-based composite material, characterized in that, include: Mesophase pitch-based carbon fibers are prepared into three-dimensional carbon fiber braids using a three-dimensional weaving process. Using methane or acetylene as a carbon source, chemical vapor deposition is performed on three-dimensional carbon fiber weaving to grow a three-dimensional graphene network in situ on the surface of the carbon fiber, thus obtaining a three-dimensional graphene / carbon fiber preform. The three-dimensional graphene / carbon fiber preform was placed in a solution containing a silver precursor, and silver oxide nanosheets were grown in situ on the surface of the three-dimensional graphene network through a hydrothermal reaction to obtain a three-dimensional graphene / carbon fiber preform modified with silver oxide nanosheets. A matrix densification treatment was performed on a three-dimensional graphene / carbon fiber preform modified with silver oxide nanosheets to obtain a three-dimensional graphene-reinforced carbon-based composite material.
2. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 1, characterized in that, The three-dimensional weaving process is selected from either three-dimensional orthogonal weaving or three-dimensional four-way weaving.
3. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 1, characterized in that, The mesophase pitch-based carbon fiber has a single filament diameter of 5–10 μm, and the porosity of the three-dimensional carbon fiber braid is 50%–80%.
4. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 1, characterized in that, The process parameters for chemical vapor deposition are: deposition temperature 800–1200℃, deposition time 10–60 min.
5. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 1, characterized in that, The carbon source gas flow rate for the chemical vapor deposition is 100–500 sccm.
6. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 1, characterized in that, The silver-containing precursor solution is one of silver nitrate solution, silver acetate solution, or silver ammonia solution, and the mass of the silver oxide nanosheets accounts for 1 to 15% of the mass of the three-dimensional graphene.
7. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 1, characterized in that, The process parameters for the hydrothermal reaction are: reaction temperature 150-200℃, reaction time 8-15h.
8. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 1, characterized in that, The matrix densification treatment employs either chemical vapor infiltration or liquid phase impregnation-carbonization.
9. The method for preparing the three-dimensional graphene-reinforced carbon-based composite material according to claim 8, characterized in that, The liquid-phase impregnation-carbonization method includes: immersing the preform in an impregnation solution of phenolic resin or mesophase pitch under vacuum for 1–4 hours, followed by carbonization at 800–1000℃ for 1–3 hours, and repeating the impregnation and carbonization process until the material density reaches 1.6–2.0 g / cm³. 3 .
10. A three-dimensional graphene-reinforced carbon-based composite material, characterized in that, The composite material is prepared by the preparation method according to any one of claims 1 to 9.